SEDENTARY LIFESTYLE: SKRINING POTENSI RISIKO KESEHATAN PADA CIVITAS AKADEMIKA UNIVERSITAS JAMBI TAHUN 2024 - Shafira, Nyimas Natasha Ayu; Enis, Rina Nofri; Puspasari, Anggelia; Maharani, Citra; Tarawifa, Susan (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2024)
ABSTRACT The sedentary lifestyle among office workers is associated with various adverse health risks, such as increased rates of metabolic disorders such as diabetes mellitus, hypertension, and dyslipidemia, as well as depression and cognitive impairment. Data from the Jambi University Clinic shows that there are still many educational staff and educators who are overweight, and awareness of getting themselves checked before health problems arise is still low. Health screening related to adverse effects due to a sedentary lifestyle, such as obesity, hypertension, and diabetes mellitus, needs to be carried out so that preventive measures and further management can be carried out. The PPM was attended by educational staff or educators at Jambi University aged 19-64, who were checked for body mass index (BMI), blood pressure, and fasting blood sugar (GDP) measurements. Before taking venous blood for GDP examination, participants must fast for 8-10 hours. The examination results are sent to service participants along with health promotion media in the form of leaflets to avoid sedentary behavior. The activity was attended by 99 people who met the criteria. From the results of BMI measurements, it was found that 8.08% were underweight, 22.2% normoweight, 8.08% overweight, and 61.62% obese. The GDP examination found that 92.93% were normal, 3.03% pre-diabetic, and 4.04% were diabetic. From blood pressure measurements, it was found that 36.36% were normal, 39.39% were pre-hypertension, and 24.24% were hypertensive. It should be noted that service participants who are underweight, overweight, pre-diabetic, and pre-hypertensive need regular follow-up evaluations to prevent worsening of their health conditions. Participants who are obese, diabetic, and hypertensive need to receive further management in the form of treatment from a doctor according to the health problems they are experiencing. Keywords: Diabetic, Hypertension, Obesity, Sedentary lifestyle ABSTRAKGaya hidup yang kurang gerak (sedentary lifestyle) di kalangan pekerja kantoran memiliki hubungannya dengan berbagai risiko kesehatan yang merugikan seperti peningkatan angka gangguan metabolism seperti diabetes mellitus, hipertensi, dan dislipidemia, serta depresi, dan gangguan kognitif. Data dari Klinik Universitas Jambi, diketahui bahwa masih banyak tenaga kependidikan maupun pendidik yang memiliki berat badan berlebih, dan kesadaran untuk memeriksakan diri sebelum timbul masalah kesehatan yang masih rendah. Skrining kesehatan terkait efek buruk yang timbul karena perilaku sedentary seperti obesitas, hipertensi dan diabetes mellitus perlu dilakukan agar dapat dilakukan tindakan preventif maupun tatalaksanalanjutan. PPM diikuti oleh tenaga kependidikan atau pendidik di Universitas Jambi berusia 19-64 tahun, dilakukan pemeriksaan Indeks massa tubuh (IMT), tekanan darah dan pengukuran gula darah puasa (GDP). Sebelum pengambilan darah vena untuk pemeriksaan GDP, peserta diwajibkan berpuasa 8-10 jam. Hasil pemeriksaan dikirimkan kepada peserta pengabdian beserta media promosi kesehatan berupa leaflet untuk menghindari perilaku sedentary. Kegiatan diikuti oleh 99 orang yang memenuhi kriteria. Dari hasil pengukuran IMT didapatkan 8.08% underweight, 22.2% normoweight, 8.08% overweight dan 61.62% obese. Dari pemeriksaan GDP didapatkan 92.93% normal, 3.03% pre-diabetik, 4.04% diabetik. Daripengukuran tekanan darah didapatkan 36.36% normal, 39.39% pre-hipertensi, 24.24% hipertensi. Hendaknya menjadi perhatian untuk peserta pengabdian yang mengalami underweight, overweight, prediabetik, dan pre-hipertensi membutuhkan evaluasi lanjutan secara berkala agar tidak terjadi perburukan kondisi kesehatan. Para peserta yang mengalami obese, diabetik, dan hipertensi perlu untuk mendapat tatalaksana lanjutan berupa pengobatan dari dokter sesuai masalah kesehatan yang dialami.Kata kunci: Diabetes, Hipertensi, Obesitas, Sedentary lifestyle